Review of pediatric head and neck pilomatrixoma. (June 2016) - Schwarz, Yehuda; Pitaro, Jacob; Waissbluth, Sofia; Daniel, Sam J.
Abstract: Introduction: Pilomatrixoma is a benign skin tumor, which is commonly found in the head and neck region. It usually presents as an isolated lesion and rarely undergoes malignant transformation. It is not uncommon for these tumors to be misdiagnosed. Objective: To review the clinical characteristics of head and neck pilomatrixomas in the pediatric population. Methods: A systematic review was completed by searching ten databases to identify studies reporting findings on pilomatrixoma in the pediatric population. Eligible articles were independently assessed for quality by two authors. Results: A total of 17 studies met the inclusion criteria totaling 318 pediatric patients. The age of diagnosis ranged from 3 months to 17 years of age. The female to male ratio was 1.65:1. In 14 articles, in which pilomatrixoma was located in the head and neck region, 76 (25%) lesions were found in the neck while 229 (75%) were present in the head region. Three articles exclusively described ophthalmologic pilomatrixoma. Even though pilomatrixoma presents with classical features, the clinical diagnostic accuracy when confronting this lesion averaged 43%. The definitive treatment was surgical excision with a very low recurrence rate. Conclusion: Head and neck pilomatrixoma in the pediatric population has a typical presentation with a low clinical diagnostic accuracy. Awareness of this lesion and its clinical appearance can improve its diagnosis. We hereby suggest a management algorithm for suspected pilomatrixoma.